2020
DOI: 10.3390/ijerph17051717
|View full text |Cite
|
Sign up to set email alerts
|

Provincial Dietary Intake Study (PDIS): Energy and Macronutrient Intakes of Children in a Representative/Random Sample of 1–<10-Year-Old Children in Two Economically Active and Urbanized Provinces in South Africa

Abstract: The double burden of malnutrition is still prevalent in South Africa, hence the importance of a dietary survey to identify risks of under-and over-nutrition. A multistage stratified cluster random sampling design was applied in two economically active provinces, Gauteng (GTG) (N = 733) and Western Cape (WC) (N = 593). Field workers completed questionnaires, and a 24 h recall with children taking part aged 1-<10-years (N = 1326). Important findings were that 71% and 74%, respectively, of 3-<6-year-olds and 6-<1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 50 publications
1
28
1
Order By: Relevance
“…For example, results from the South African Provincial Dietary Intake Survey in 1 to >10-year-old children showed that salty snacks contributed a third of total energy intake (maize porridge contributed most to total energy intake), while also being the top source of total fat and saturated fat. Granulated sugar (e.g., sugar added to hot drinks) was found to be the third highest contributor to total carbohydrate intake [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, results from the South African Provincial Dietary Intake Survey in 1 to >10-year-old children showed that salty snacks contributed a third of total energy intake (maize porridge contributed most to total energy intake), while also being the top source of total fat and saturated fat. Granulated sugar (e.g., sugar added to hot drinks) was found to be the third highest contributor to total carbohydrate intake [49].…”
Section: Discussionmentioning
confidence: 99%
“…Two free text questions probed which food items/dishes and snacks/drinks household respondents liked and disliked the most. The availability of household food items was determined via a household inventory adapted from a previous study [49]. In instances where the household respondent was illiterate, learners were instructed to assist with the completion of the self-administered questionnaire.…”
Section: Household Questionnairementioning
confidence: 99%
“…It is thus recommended that the Department of Basic Education find ways to enforce this mandate. Considering the overall low intake of vegetables and fruit in South African children [35] and the importance of eating sufficient amounts thereof to reduce the risk for developing certain non-communicable diseases and micronutrient deficiencies [36], the school meal together with good quality nutrition education can be a vehicle for increasing the intake of fruit and vegetables in learners.…”
Section: Discussionmentioning
confidence: 99%
“…Prentice et al, [43] reported that breastmilk contributed significantly to fat intake up to 17 months (50%E), which declined thereafter to 30% and 15% at 17 and 24 months, respectively. In a more recent study from South Africa, Steyn et al, [45] reported that breastmilk contributed to 18.7% of total energy intake up to 3 years. Thus, in infancy and early childhood, breastmilk intake can contribute significantly to intake of energy and fat.…”
Section: Contribution Of Breastmilk To Fat and Fatty Acid Intakementioning
confidence: 96%